MANAJEMEN PANTI ASUHAN DALAM PERSPEKTIF HENRI FAYOL: ( STUDY KASUS PANTI ASUHAN USMAN BIN AFFAN ) - Evi Zubaidah (UIR Press, 2016)
Usman Bin Affan orphanage is located at Gedog, Ngluwar, Magelang. Its presence is enough to providebenefits to the surrounding community, especially for orphans who can not afford. Besides, theorphanage Usman Bin Affan has had a good achievement that is the first winner in Magelang Districtand Second Place in Central Java province. Foster children who live orphanage Usman Bin Affan quite alot of about 100 children who came from the island of Java and Sumatra. As orphanages that are wellknown and have the advantage of another orphanage rightly learn how management implemented by theorphanage, orphanage So Usman Bin Affan will be a reference to apply management in particular for themanagement of the orphanage. Results of research on Management Orphanage Uthman Bin Affan in the perspective of Henri Fayol are planning, Orphanage Uthman Bin Affan already using ways that modernplanning involving foster children, so its not just a top down but also bottom up. Organizing,implementation organizing committee conducted an orphanage run well, which includes materials,equipment, capital and personal. But there are aspects that are not organized that equipment, because theboard of the orphanage is still limited organize personalized according to the authority of the boardrespectively. But it is still not visible effort organizing the equipment in detail. Command, leaders andadministrators Orphanage Uthman Bin Affan always give orders in accordance with what has beenestablished so always make every effort to optimize the work of its units. Coordination, OrphanageUsman Bin Affan can be run in coordination with other parties. But coordination in the institution has notbeen established as well as the practice is still running kulturan kooordinasi and informal. Controlling,leaders and administrators Orphanage Uthman Bin Affan basically have to supervise properly.Everything is always summarized in a written report submitted to the leadership to the next and arereported every year, usually three months after closing the year.